Spleen stiffness measurement as a non-invasive assessment in patients with portal hypertension - Jie Li; Chao Wu; Jiacheng Liu; Xiaoming Xu; Yixuan Zhu; Fajuan Rui (eGastroenterology)
For patients with advanced chronic liver disease who are in a compensated state, the development of portal hypertension (PHT) can lead to a heightened risk of hepatic decompensation and mortality. This underscores the importance of timely and appropriate treatment to manage the condition and prevent further complications. The current gold standard procedure for determining PHT is the hepatic venous pressure gradient, but its invasiveness limits its usage in clinical practice and larger trials of novel agents. The current clinical demand for accurate, validated and non-invasive methods to assess the severity of PHT remains unmet. One potential non-invasive option is tissue elastography, which examines the elastic behaviour of tissue after a force has been applied. This method involves quantifying alterations in the biomechanical properties of the liver or spleen in patients with cirrhosis. Available methods are various, including transient elastography, shear wave elastography, acoustic radiation force impulse and magnetic resonance elastography. Importantly, the measurement of spleen stiffness appears to outperform liver stiffness as a direct and dynamic indicator of portal pressure, offering the potential to monitor PHT and evaluate improvements in PHT as a marker for clinical outcomes.